1999
DOI: 10.5005/jcdp-1-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Root Coverage Using Alloderm® Acellular Dermal Graft Material

Abstract: This report describes a surgical technique for root coverage using an acellular dermal graft material and a coronally positioned flap. Video clips of a root coverage surgery are included using the graft material to cover multiple teeth in the same quadrant. Three additional completed cases are presented in which a mean root coverage of 97% was achieved, resulting in 100% coverage on 9 of 11 teeth. The results from this case series conform with the available evidence on the use of acellular dermal graft materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 15 publications
0
16
0
3
Order By: Relevance
“…Therefore, an acellular dermal graft (ADM) has been used as an alternative source of donor tissue sites in this type of surgery. [26][27][28][29][30][31][32][33] The material provides an unlimited supply of graft material that could be particularly helpful when treating multiple recession sites. 33 The present study compared the treatment of Class I gingival recessions using CPF with or without ADM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an acellular dermal graft (ADM) has been used as an alternative source of donor tissue sites in this type of surgery. [26][27][28][29][30][31][32][33] The material provides an unlimited supply of graft material that could be particularly helpful when treating multiple recession sites. 33 The present study compared the treatment of Class I gingival recessions using CPF with or without ADM.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an acellular dermal graft (ADM) has been used as a substitute for the palatal donor sites to increase the width of keratinized tissue around teeth, [16][17][18][19][20][21][22][23][24] for the treatment of alveolar ridge deformities, 25 and for root coverage procedures. [26][27][28][29][30][31][32][33] In vitro as well as clinical studies suggested that ADM is an acellular, nonimmunogenic scaffold that heals by repopulation and revascularization, rather than through a granulation process. 34,35 Previous studies compared the results obtained with ADM (test group) and the SCTG (control group) for the treatment of gingival recessions.…”
mentioning
confidence: 99%
“…Recently, an acellular dermal matrix graft (ADM) has been used as a substitute for the autogenous graft for root coverage procedures (Harris & Harris 1994, Dodge et al 1998, Henderson et al 1999, Tal 1999, Aichelmann‐Reidy et al 2001, Novaes et al 2001, Tal et al 2002, Côrtes et al 2004, Gapski et al 2005). The previous studies comparing ADM and the SCTG showed no significant differences in recession reduction between the procedures (Harris & Harris 1994, Aichelmann‐Reidy et al 2001, Novaes et al 2001, Paolantonio 2002, Tal et al 2002).…”
mentioning
confidence: 99%
“…9,10 More recent approaches have included human-derived intact tissue complexes, including acellular dermal matrix (Alloderm; LifeCell, Branchburg, NJ) and pericardium (Pericardium; Tutoplast, Neunkirchen, Germany). [11][12][13][14][15] However, the need for tissue donated from a human source remains a limiting factor with Alloderm. Although a number of clinical studies have documented the effectiveness of periodontal GTR, [16][17][18][19][20] few studies have reported the long-term outcome of these therapies.…”
Section: Introductionmentioning
confidence: 99%